2002
DOI: 10.1021/jf010855a
|View full text |Cite
|
Sign up to set email alerts
|

Interactions between Flavonoids and Proteins:  Effect on the Total Antioxidant Capacity

Abstract: Flavonoids are potent antioxidants. It is also known that flavonoids bind to proteins. The effect of the interaction between tea flavonoids and proteins on the antioxidant capacity was examined. Their separate and combined antioxidant capacities were measured with the Trolox equivalent antioxidant capacity (TEAC) assay. It was observed that the antioxidant capacity of several components of green and black tea with alpha-, beta-, and kappa-casein or albumin is not additive; that is, a part of the total antioxid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

20
191
1
4

Year Published

2007
2007
2018
2018

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 402 publications
(216 citation statements)
references
References 16 publications
20
191
1
4
Order By: Relevance
“…The addition of milk did not decrease the in vitro antioxidant potential of tea, which is in agreement with one previous study (17), but in contrast with another (14). Our results suggest that the formation of milk protein-polyphenol complexes does not compromise the antioxidant potential of the beverage.…”
Section: Discussionsupporting
confidence: 93%
“…The addition of milk did not decrease the in vitro antioxidant potential of tea, which is in agreement with one previous study (17), but in contrast with another (14). Our results suggest that the formation of milk protein-polyphenol complexes does not compromise the antioxidant potential of the beverage.…”
Section: Discussionsupporting
confidence: 93%
“…It is well known that EGCg binds to casein and serum proteins, resulting in a decrease in its antioxidant (18) and anti-microbial activities (9). Proline groups in proteins are known to have a strong affinity for the hydroxyl group of EGCg (19). In the present study, a marked decrease in EGCg concentration was observed after the protease and conjugase treatments, which contained higher amounts of protein compared to the a-amylase treatment.…”
Section: Discussionsupporting
confidence: 49%
“…They also reported that the antioxidant activity and phenol content increased on heat treatment (65°C/30 min) of skim milk. This could be due to excess phenol released due to breaking off bonds between polyphenols and milk protein in the complexation compound or may be due to formation of radical scavenging complexation compounds formed by covalent interaction between oxidised phenolic compounds and amino acid residues of proteins (Arts et al 2001;Ridle and Hagerman 2001;Rohn et al 2004). Karaaslan et al (2011) also found higher antioxidant power in grape extract fortified yogurt with higher anthocyanin content than control yogurt.…”
Section: Total Antioxidant Capacity (Tac) By Abts Methodsmentioning
confidence: 97%